Analysis of energy integration opportunities in the retrofit of a milk powder production plant using the Bridge framework. (15th December 2021) - Bergamini, Riccardo; Moussavi, Alireza; Shahhosseini, Hamid Reza; Nguyen, Tuong-Van; Bellemo, Lorenzo; Elmegaard, Brian; Stuart, Paul
Abstract: The "bridge framework" is a systematic decision-making support tool for process integration retrofit of industrial plants, which proposes the use of "bridge analysis" in a structured fashion. Its potential of rigorously analysing industrial processes has been discussed, but no applications on actually operating plants considering process constraints have been presented to date. The paper demonstrates the capabilities of the bridge framework in analysing an actually operating milk powder production plant. Its step-by-step application is thoroughly described and discussed, highlighting inherent strengths and weaknesses of the method. Moreover, a clarification of the "energy transfer diagram" is proposed, distinguishing avoidable and unavoidable heat degradation in the heat exchanger network by introducing the concept of "limit heat transfer interface". The results proved that the bridge framework is a rigorous tool, which provided valuable insight to the analyst aiding the open-ended decision-making activities related to the retrofit of both process operations and heat exchanger network. Seven design proposals were identified, out of which the best resulted in 54000 €/y of economic saving with an internal rate of return of 34% and a minimum risk level. The step-by-step application of the method demonstrated that good engineering judgement is critical for achieving beneficial solutions. Expertise on process operations as well as energy analytics is essential for completing the project. Finally, the concept of "limit heat transfer interface" allowed to completely link bridge analysis and pinch analysis and to clarify the meaning of the "grand composite curve". Highlights: The Bridge framework is applied to an existing milk powder production plant. The method is proven valuable supporting decision-making activities in retrofit projects. The energy transfer diagram is extended displaying avoidable heat degradation. The terminology used in displaying the grand composite curve is clarified. An algorithm for calculating the energy-saving potential of bridges is proposed.